Make-Believe: Parafiction and Plausibility. - Lambert-Beatty, Carrie (October)
This essay discusses a category of art called parafictional and focuses on one such project by artist Michael Blum, who made up the obscure historical figure Safiye Behar, a Turkish Jewish woman who supposedly had a lifelong affair with Mustafa Kemal Ataturk, founder of the Turkish Republic. It cites other fakes such as satirist Stephen Colbert, whose television persona is a conservative talk show host, comedian Andy Kaufman, and the fake conversion of Vienna's Karlsplatz into Nikeplatz.